Implementasi Kurikulum Pembiasaan Ibadah dalam Pembentukan Karakter Religius Peserta Didik di SMP IT Ma’wattaibin Banjarejo - Khoirul Arifin; Izzal Fauzi; Sutriyaningsih Sutriyaningsih; Sita Acetylena (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the implementation of the worship habituation curriculum in the formation of students' religious character at SMP IT Ma'Wattaibin Banjarejo. This study uses a qualitative approach with a case study type. Data was collected through in-depth interviews, observations, and documentation involving principals, teachers, and students. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawing with source triangulation techniques and techniques to maintain the validity of the data. The results of the study show that the worship habituation curriculum is implemented in a structured and integrated manner in school culture through congregational prayer activities, daily prayers, recitals of the Qur'an, and habituation of Islamic manners. The implementation of the curriculum contributes significantly to the formation of students' religious character, especially in the aspects of discipline, responsibility, and awareness of worship. In addition, the habit of worship also has a positive impact on the formation of spiritual attitudes, social behavior, and harmonious relationships between students and the school environment. This study concludes that the worship habituation curriculum managed as a school-based curriculum has a strategic role in strengthening the religious character of students in integrated Islamic schools.